A review on the diabetic retinopathy assessment based on retinal vascular tortuosity - Mustafa N.B.A.; Zaki W.M.D.W.; Hussain A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Ophthalmology; Signal processing; Diabetic retinopathy; Eye disease; Quantitative method; Retinal vascular tortuosity; Visual loss; Eye protection